Mengetahui Penyakit Tekanan Darah Tinggi (Hipertensi) - Durra Sadrina Hasan; Tamaulina Br. Sembiring (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
An increase in systolic and diastolic blood pressure is known as hypertension.When people are unaware of how to effectively treat their hypertension, the prevalence of high blood pressure (hypertension) can lead to a host of issues.Hypertension, or high blood pressure, is one of the leading causes of death from cardiovascular disease.As many as 26.5% of Indonesian people were hypertensive in 2013. Premature mortality, heart failure, and neurological diseases are all increased by hypertension. Factors related to socioeconomic status, age, and lifestyle can all contribute to the development of hypertension.As we get older, our big blood arteries undergo structural changes that raise cytolic blood pressure and constrict the channel lumen, increasing the chance of developing hypertension.Google Schoolar, published between 2019 and 2021, is utilized in this research.This research aims to better understand hypertension, or high blood pressure.High Blood Pressure (Hypertension) is the subject of this journal's qualitative research, which consists of reading a variety of publications.The general population has accurate information regarding hypertension, according to this journal's findings.